Improvement of neuropathology and transcriptional deficits in CAG 140 knock-in mice supports a beneficial effect of dietary curcumin in Huntington's disease - Hickey, Miriam A (BioMed Central, 2012)
BACKGOUND: No disease modifying treatment currently exists for Huntington's disease (HD), a fatal neurodegenerative disorder characterized by the formation of amyloid-like aggregates of the mutated huntingtin protein. Curcumin is a naturally occurring polyphenolic compound with Congo red-like amyloid binding properties and the ability to cross the blood brain barrier. CAG140 mice, a knock-in (KI) mouse model of HD, display abnormal aggregates of mutant huntingtin and striatal transcriptional deficits, as well as early motor, cognitive and affective abnormalities, many months prior to exhibiting spontaneous gait deficits, decreased striatal volume, and neuronal loss. We have examined the ability of life-long dietary curcumin to improve the early pathological phenotype of CAG140 mice. RESULTS: KI mice fed a curcumin-containing diet since conception showed decreased huntingtin aggregates and increased striatal DARPP-32 and D1 receptor mRNAs, as well as an amelioration of rearing deficits. However, similar to other antioxidants, curcumin impaired rotarod behavior in both WT and KI mice and climbing in WT mice. These behavioral effects were also noted in WT C57Bl/6 J mice exposed to the same curcumin regime as adults. However, neither locomotor function, behavioral despair, muscle strength or food utilization were affected by curcumin in this latter study. The clinical significance of curcumin's impairment of motor performance in mice remains unclear because curcumin has an excellent blood chemistry and adverse event safety profile, even in the elderly and in patients with Alzheimer's disease. CONCLUSION: Together with this clinical experience, the improvement in several transgene-dependent parameters by curcumin in our study supports a net beneficial effect of dietary curcumin in HD.